INJURY MECHANISMS AND SURVIVAL IN FIGHTER AIRCRAFT EJECTIONS BASED ON A SYSTEMATIC REVIEW - Muhammad Hilmi Wiratama; Indri Hapsari Susilowati (International Review of Practical Innovation, Technology and Green Energy (IRPITAGE), 2026)
The ejection seat system in fighter aircraft is a safety technology that plays a crucial role in saving pilots in flight emergencies. However, the high vertical acceleration during the early ejection phase and the propulsion phase exposes pilots to significant axial loads, increasing the risk of spinal cord injury. This systematic review was conducted following PRISMA 2020 guidelines by reviewing literature from Scopus (n = 20) and PubMed (n = 12) databases. After screening and assessing eligibility, 15 studies were included in the qualitative synthesis. The results showed that axial compression of the spine during the early ejection phase was the most common injury mechanism. Vertebral fractures, particularly in the thoracolumbar segment, were the most frequently reported acute injuries. In addition to biomechanical factors, pilot survival is also influenced by operational factors, particularly the timing of the ejection decision and the altitude at which ejection was initiated. Delayed ejection has been reported to be associated with an increased risk of fatality. Thus, injury severity and survival are influenced by the interaction between axial biomechanical loads and operational decisions in emergency situations. These findings demonstrate the importance of an integrated safety approach through the development of ejection system designs, improvements to operational training, and monitoring the occupational health of fighter aircraft crews.